2015
DOI: 10.1007/s12237-015-9949-z
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Residence Time Controls on an Estuarine Harmful Algal Bloom: Modeling Hydrodynamics and Alexandrium fundyense in Nauset Estuary

Abstract: A highly resolved, 3-d model of hydrodynamics and Alexandrium fundyense in an estuarine embayment has been developed to investigate the physical and biological controls on a recurrent harmful algal bloom. Nauset estuary on Cape Cod (MA, USA) consists of three salt ponds connected to the ocean through a shallow marsh and network of tidal channels. The model is evaluated using quantitative skill metrics against observations of physical and biological conditions during three spring blooms. The A. fundyense model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 51 publications
0
29
1
Order By: Relevance
“…Observational studies in the NW Atlantic have described shifts in A. fundyense bloom dynamics and duration that are related to interannual temperature variability (6,7,22). A compilation of A. fundyense bloom dynamics from the Bay of Fundy indicated that, consistent with our findings, the first appearance of A. fundyense cells was, on average, 3 wk earlier in the first decade of this century compared with the final 12 y of the 20th century and that maximum cell densities during blooms increased more than threefold over the same time period (23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Observational studies in the NW Atlantic have described shifts in A. fundyense bloom dynamics and duration that are related to interannual temperature variability (6,7,22). A compilation of A. fundyense bloom dynamics from the Bay of Fundy indicated that, consistent with our findings, the first appearance of A. fundyense cells was, on average, 3 wk earlier in the first decade of this century compared with the final 12 y of the 20th century and that maximum cell densities during blooms increased more than threefold over the same time period (23).…”
mentioning
confidence: 99%
“…Further, this significant correlation provides quantitative evidence that the modeled bloom season presented by this study accurately tracked the dynamics of Alexandrium populations in this region. Beyond the effects on the growth of vegetative cells, warming temperatures will also promote an earlier emergence of cysts that provide the inoculum for A. fundyense blooms (22,24).…”
mentioning
confidence: 99%
“…However, high-frequency, in situ observations using the IFCB in Salt Pond (Brosnahan et al, submitted) show net population growth rates that were in excess of those expected from culture-derived growth rates. This discrepancy is under active investigation, but highlights the difficulties and uncertainties in calculating growth rates from a limited number of samples (weekly) during a bloom in a tidal embayment, even ones as retentive as Salt Pond and Mill Pond (Ralston et al, in press). …”
Section: Discussionmentioning
confidence: 99%
“…Dinoflagellates form subsurface aggregations and are selectively retained relative to the tidal exchange in the NMS salt ponds due to avoidance of highly illuminated surface waters by diel vertical migration (Anderson and Stolzenbach, 1985), and the bathymetric constraints on flow and suppression of mixing by stratification (Ralston et al, in press). Thus, the NMS provided an opportunity to study population dynamics over the course of a natural A. fundyense bloom in a single location where physical advection of dinoflagellate populations was relatively minimal.…”
Section: Introductionmentioning
confidence: 99%
“…Transport time scales, such as residence time-the time taken by a water parcel or its constituents to leave a defined region of interest through its outlets to the sea [1,2], or flushing time-a bulk or integrative parameter that describes the general exchange characteristics of a waterbody without its spatial distribution [3]-are usually used as first-order metrics of transport to assess the health and integrity of estuarine and coastal ecosystems. For example, the concept of residence time has been used to study pollutant concentrations [4], distributions of plankton [5,6], harmful algal blooms [7,8], pelagic bacteria [9], and dissolved nutrients [10,11].…”
Section: Introductionmentioning
confidence: 99%